Realitas Korupsi Dalam Konstruksi Media Massa Lokal Sebuah Studi Critical Discourse Analysis atas Editorial Surat Kabar Flores Pos dan Pos Kupang di Provinsi NTT - Jonas Klemens Gregorius Dori Gobang (Jurnal InterAct, 2013)
The reality in NTT with poor people and corrupt government urged the researcher to analyze position of the media (local press). Using Teun A.van Dijk‘s Critical Discourse Analysis (CDA) model,thedata collected were editorial  text  of  newspapers,  cognition  data  of  editorial  writer  and  social context data. Both newspapers, Flores Pos and Pos Kupang provided different pattern from the media ownership aspect. Flores Pos tended to be more independent in producing editorial text, while Pos Kupang tended to limit writer independence in producing editorial text. The note confirms that reality of today media can be coopted by capital owner, market or state interest.